Endoscopic surgery for papillary thyroid microcarcinoma: cases review and investigation of technique dissemination in China - Liang, Yinghui; Xu, Shuangta (Frontiers in Endocrinology, 2025)
IntroductionThyroid cancer has become one of the most common types of cancer, with microcarcinomas accounting for more than 50% of all newly diagnosed thyroid cancers. Endoscopic thyroid surgery, which relocates the incision to a less visible area of the body, offers significant postoperative cosmetic benefits and has been widely used in the treatment of thyroid microcarcinomas. This study conducts a retrospective case analysis and questionnaire survey to provide clinical reference by statistically analyzing the development of endoscopic techniques in China over the past five years.Materials and methodsThis study included cases of thyroid microcarcinoma surgeries performed in our hospital from January 2018 to March 2020. Postoperative follow-up was conducted using the THYCA-QoL questionnaire. A network questionnaire survey was carried out through the Chinese Society of Oncoplastic Endocrine Surgeons targeting its members and other institutions performing endoscopic thyroid surgeries. The data was analyzed to obtain relevant results.ResultsThe complications were comparable between the endoscopic and open surgery groups. The incidence of neck discomfort was higher in the open surgery group compared to the endoscopic group (21.92% vs. 13.38%). Scar formation was also more noticeable in the open surgery group (23.74% vs. 17.2%). The local recurrence rates were similar between the two groups (1.27% vs. 1.37%). Over 85% of the surveyed institutions reported endoscopic thyroid surgery via trans-breast approach, while the trans-axillary approach showed the fastest growth over the past five years. Most institutions (approximately 80%) performed fewer than 300 endoscopic thyroid surgeries annually. Additionally, in most institutions (around 67%), endoscopic thyroid surgeries accounted for less than 20% of the total thyroid surgeries performed annually. The most frequently questioned issues regarding the trans-breast and trans-axillary approaches were the completeness of central lymph node dissection (with 66.78% and 40.46% of respondents, respectively, considering the lymph node dissection to be incomplete). Furthermore, about 20%-30% of the surveyed institutions believed that endoscopic surgery was more traumatic and associated with a higher incidence of post-thyroidectomy syndrome (PTS).ConclusionFor papillary thyroid microcarcinoma, endoscopic surgery demonstrates comparable efficacy to traditional open surgery, with no significant differences observed in 5-year recurrence and survival rates during follow-up. However, the safety and reliability of various endoscopic approaches for thyroid cancer surgery remain questionable, particularly regarding the thoroughness of central compartment lymph node dissection, as indicated by surveys on the implementation of endoscopic thyroid surgery over five consecutive years. More long-term follow-up data are required to validate these outcomes. Therefore, we recommend that preoperative lymph node positivity should be considered a contraindication, and patients with postoperative pathological confirmation of lymph node metastasis warrant closer clinical monitoring and intensive follow-up.